Medan Area Battle Educational Game Using Branching Narrative and Turn-Based Tactical Combat - Maulana Fauzan; Chrystia Aji Putra; Andreas Nugroho Sihananto (bit-Tech, 2025)
The rapid advancement of digital technology has created new opportunities for integrating interactive media into history education, a subject often perceived as passive and less engaging. Addressing the lack of educational games that combine narrative with strategic simulation, this study develops and evaluates Medan Area Battle, a 2D action role-playing game that introduces a dual-pedagogical mechanism through branching narrative and turn-based tactical combat. This integration is designed to allow students to experience historically grounded decision-making while simultaneously engaging in strategic reasoning with the events of the Medan Area Battle. A design-based research framework guided the development process through requirement analysis, design, implementation, and user testing. The evaluation involved twenty-five junior high school students, providing insight into the game's effectiveness. Learning performance was measured through pre-test and post-test assessments, while user experience was examined using Game User Experience Satisfaction Scale-18 (GUESS-18). Two additional dimensions Branching Narrative and Tactical Combat were incorporated to capture the unique interaction patterns introduced by the game’s narrative and strategic systems. Statistical analysis employed the Shapiro–Wilk test, Wilcoxon Signed Rank test, and Cronbach’s Alpha reliability testing. Results indicated a significant improvement in learning outcomes, with mean scores rising from 60.80 to 85.60 (p = 0.000767). The overall GUESS-18 rating of 4.15 (“Very Good”), alongside high scores in Educational (4.30) and Tactical Combat (4.27), suggests strong user engagement. These findings demonstrate that integrating narrative choice with tactical gameplay offers effective and theoretically grounded approach enhancing students’ cognitive understanding and motivation in history learning.